Developing legal framework for social enterprise business entity in Malaysia - Mohd Shahril Nizam Md Radzi
The emergence of social enterprise as a new paradigm in social development has gained attention from numerous scholars in various disciplines. Through the concept of innovation, social enterprise exists in-between three economic sectors (Government, Private Sector and Non- Profit Organization) to meet societal demands and needs effectively. Social enterprise operates with dual missions to serve social needs through commercial activities and providing limited profit distribution. In Malaysia, the development of social enterprise is still left behind the developed countries such as the United Kingdom, the United States and Italy. The absence of a specific business vehicle for social enterprise in Malaysia is indeed a problem that has forced social entrepreneurs to operate their business through various existing business entities. Unfortunately, those business entities do not fit with the nature of their business operations. Further, several issues such as governance and tax treatment have arisen and might threaten their sustainability. Therefore, the objectives of this research are to analyze suitable business structure and tax treatment for social enterprise and to propose a legal framework of a new business entity for social enterprise in Malaysia .This research adopted a legal doctrinal methodology as it is relevant to evaluate and analyze legal theories for the development and their application to social enterprise. This type of methodology also employed a content analysis approach, based on historical, philosophical and comparative perspectives. As for data collection, this research resorted to data from primary and secondary sources in law. The data from primary sources consist oflegal statutes and cases from respective countries such as the United Kingdom, the United States and Malaysia, whereas the data from secondary sources include law books, journals, newspapers' articles and reports, conference proceedings and other relevant legal documents. All of the above data were gathered through library research from legal database, websites or written materials. A special reference is made to the Community Interest Company Regulation 2005 in the United Kingdom being the foremost country which enacted a specific business vehicle for social enterprise. Having a comprehensive legal structure, Community Interest Company in United Kingdom is the best choice for comparative study. It is found that a corporate structure is the most appropriate form for social enterprise's business entity in Malaysia. For that particular purpose the Concession and Purpose theories of corporate personality are utilized as legal justifications for establishment of this new business entity. These two theories discuss and emphasize on power of the state to create any corporate body for a specific purpose. In addition, a flexible approach of tax treatment is needed to support development of this new corporate business entity. Through the Concession and Purpose theories of corporate personality, a new corporate entity should be established and known as Public Interest Corporation. This specialized corporate entity will be able to facilitate the operation of social enterprise and ensure sustainability of the entity. It will also act as one of the country's economic engine that promote social and community development.